Measurement of charm and beauty production in deep inelastic ep scattering from decays into muons at HERA - Chekanov, S; Derrick, M; Magill, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Bellagamba, L; Boscherini, D; et al. (2009)
The production of charm and beauty quarks in ep interactions has been measured with the ZEUS detector at HERA for squared four-momentum exchange Q2>20 GeV2, using an integrated luminosity of 126 pb-1. Charm and beauty quarks were identified through their decays into muons. Differential cross sections were measured for muon transverse momenta pTμ > 1.5 GeV and pseudorapidities -1. 6<ημ>2. 3, as a function of pTμ >, ημ, Q2 and Bjorken x. The charm and beauty contributions to the proton structure function F2 were also extracted. The results agree with previous measurements based on independent techniques and are well described by QCD predictions. © Springer-Verlag / Società Italiana di Fisica 2009.